The Effects of Component Tolerances on the Thermo-Mechanical Reliability of SOFC Stacks. (30th May 2017) - Greco, Fabio; Nakajo, Arata; Wuillemin, Zacharie; Van herle, Jan
Abstract : The reliability of solid oxide fuel cell (SOFC) systems is closing the gap to meet the requirements for market implementation. Finite-element (FE) stack models, typically used for stack reliability analyses, commonly consider idealized components. In reality, dimensions and geometry of the produced stack components have statistical variations. The resulting variability in shape is expected to have an impact on the distribution of the contact pressure over the cell active area. In this study, the initial deformation of the metallic interconnect (MIC) is implemented in the stack model. The simulation starts with the simulation of the stack production and qualification. The results of this first calculation are used to simulate either thermal cycling or prolonged continuous operation. The distribution of the simulated contact pressure on the active area is found to evolve differently during thermal cycling and operation, if the initial deformation of the MIC is included in the stack model.